Fe–Co controlled super-hygroscopic hydrogels toward efficient atmospheric water harvesting. Issue 48 (29th November 2022) - Wu, Hangfei; Xiong, Yuli; Yu, Duohuan; Yang, Peixin; Shi, Huihui; Huang, Lu; Wu, Yali; Xi, Mufeng; Xiao, Peng; Yang, Lin
Abstract : A super-hygroscopic bimetallic hydrogel with high water uptake and low desorption temperature is reported, providing an efficient strategy for directly harvesting freshwater from atmosphere. Abstract : Extracting atmospheric moisture for freshwater production is an appealing way to mitigate the global water crisis. However, the low moisture sorption capacity and high desorption temperature are the major bottlenecks for efficient atmospheric water harvesting. Herein, we develop a transition metal super-hygroscopic hydrogel by an economical strategy, which is constructed through a facile coordination between metal salts and ethanolamine. When the empty electron orbital of the metal ion is coordinated with the lone electron pair of nitrogen or oxygen atom, the water active sorption site is formed. A single water layer is bonded on the sites by a coordination effect, followed by physical interaction with water to form multi-layer structures. The Fe and Co ions in the hydrogel function as dual sorption sites to capture moisture, which can harvest additional water by the synergistic effect of bimetals. As a result, the bimetal hydrogel contributes to a high water uptake of 5.22 g g −1 at 95% RH, triggering the desorption process by one solar intensity due to its low desorption temperature (≤50 °C).